2020
DOI: 10.1002/kpm.1650
|View full text |Cite
|
Sign up to set email alerts
|

Constructing customer knowledge in knowledge‐intensive customer relationships

Abstract: Knowing your customers and their needs is a topic that has attracted increasing interest in the business and academic worlds. In line with this, constructing customer knowledge has come under examination in this study. A firm's ability to construct customer knowledge creates solid ground for responding better to its customers' needs. In the business‐to‐business markets, customers are demanding increasingly knowledge‐intensive services. Therefore, examining the topic is particularly important in this specific c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…This subsequently supports the firm's relationship with the customer and enables them to customise offerings and adjust value propositions accordingly. Furthermore, with customer knowledge, companies will find it easier to communicate the value they can offer clients (see e.g., Heikka, 2020), and the findings of this study highlight that a genuine willingness to collaborate and a customer‐oriented mindset are essential characteristics for developing meaningful KIBS customer relationships in which both parties adjust their processes and which is ultimately based on excellent customer knowledge.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…This subsequently supports the firm's relationship with the customer and enables them to customise offerings and adjust value propositions accordingly. Furthermore, with customer knowledge, companies will find it easier to communicate the value they can offer clients (see e.g., Heikka, 2020), and the findings of this study highlight that a genuine willingness to collaborate and a customer‐oriented mindset are essential characteristics for developing meaningful KIBS customer relationships in which both parties adjust their processes and which is ultimately based on excellent customer knowledge.…”
Section: Discussionmentioning
confidence: 83%
“…At the beginning of a project, it is vital that the information necessary to carry it out successfully is communicated transparently, creating a basis for the co-creation of value between the firm and its clients. Relatedly, it is crucial to understand the customer and construct knowledge about them (see e.g., Heikka, 2020). The three case firms in this study built their respective knowledge bases using similar basic communication practices, such as collaboration at face-to-face meetings between the firm and the client, which supports the existing literature (see e.g., Bidian et al, 2022), but this study also found many other contributory factors, such as in-house meetings and careful documentation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the value created by PSFs is mainly studied at a point when a relationship has already been formed between the firm and the customer (Pemer and Skjølsvik, 2019), leaving the pre-purchasing stages insufficiently examined. Moreover, the literature on B2B professional services is relatively fragmented across a range of discussions in multiple research areas, including capabilities (Janssen et al , 2018); customer relationships (Cabigiosu and Campagnolo, 2019; Casidy and Nyadzayo, 2019; Growe, 2019; Heirati et al , 2019); innovation and new service development (Santos-Vijande et al , 2013); knowledge construction (Heikka, 2020); modularity (Cabigiosu and Campagnolo, 2019; Nätti et al , 2017; Heikka et al , 2018); purchasing (Bonamigo et al , 2022; Heikka and Mustak, 2017; Nyadzayo et al , 2020); value co-creation (Kohtamäki and Partanen, 2016; Mustak, 2019); and value propositions (Baumann et al , 2017; Heikka and Nätti, 2018).…”
Section: Introductionmentioning
confidence: 99%